Association between remnant cholesterol and heart failure: A prospective cohort study - Liu, Heng; Zhang, Jing; Li, Zhangbin; Liu, Jie; Lian, Shuping; Le, Jianhua (Frontiers in Cardiovascular Medicine, 2022)
Background: Elevated remnant cholesterol (RC) is associated with a higher risk of various cardiac diseases. Heart failure (HF) usually occurs at the end stage of various cardiac diseases. However, there is limited research on the association between RC and the risk of HF. Therefore, we aimed to provide relevant evidence by determining whether a high RC level also influences the risk of HF. Methods: In this secondary analysis of the Atherosclerosis Risk in Communities (ARIC) study, we included 12,595 participants without coronary heart disease. We determined the association of the RC level as a continuous or categorical variable with the risk of HF using the multivariable-adjusted Cox proportional hazards models and restricted cubic spline curve. Results: During a median follow-up of 22.5 years, 2,029 (16.1%) cases of HF occurred in all included participants. Compared with participants in the RC < 0.50 mmol/L group, the adjusted hazard ratio (HR) for HF increased progressively in participants with the RC level of 0.50 to 0.99 mmol/L, 1.00 to 1.49 mmol/L, and ≥ 1.50 mmol/L, from 1.17 (95% confidence interval [CI]: 1.05-1.30) to 1.27(95% CI: 1.08-1.49) and to 1.50 (95% CI: 1.14-1.97) (P for trend < 0.001). Cubic spline curves also revealed that the risk of HF increased with the RC level. Conclusions: In the general population without coronary heart disease, a higher level of RC was significantly associated with a higher risk of HF, indicating that a higher RC level might be a potential risk factor for HF. Therefore, the management of blood cholesterol to reduce the risks of HF should focus not only on the traditional blood lipid parameters but also on the RC level.